Differential Identification of Mycobacterial Species Using High-Resolution Melting Analysis - Khosravi, Azar D.; Hashemzadeh, Mohammad; Hashemi Shahraki, Abdolrazagh; Teimoori, Ali (Frontiers in Microbiology, 2017)
Infections caused by nontuberculous mycobacteria (NTM) is increasing wordwide. Due to the difference in treatment of NTM infections and tuberculosis, rapid species identification of mycobacterial clinical isolates is necessary for the effective management of mycobacterial diseases treatment and their control strategy. In this study, a cost-effective technique, real-time PCR coupled with high-resolution melting (HRM) analysis, was developed for the differentiation of Mycobacterial species using a novel rpoBC sequence. A total of 107 mycobacterial isolates (Nine reference and 98 clinical isolates) were subjected to differentiation using rpoBC locus sequence in a real-time PCR-HRM assay scheme. From 98 Mycobacterium clinical isolates, 88 species (89.7%), were identified at the species level by rpoBC locus sequence analysis as a gold standard method. M. simiae was the most frequently encountered species (41 isolates), followed by M. fortuitum (20 isolates), M. tuberculosis (15 isolates), M. kansassi (10 isolates), M. abscessus group (5 isolates), M. avium (5 isolates), and M. chelonae and M. intracellulare one isolate each. The HRM analysis generated 6 unique specific groups representing M. tuberculosis complex, M. kansasii, M. simiae, M. fortuitum, M. abscessus-M. chelonae group and M. avium complex. In conclusion, this study showed that the rpoBC-based real-time PCR followed by HRM analysis could differentiate the majority of mycobacterial species that are commonly encountered in clinical specimens.